Penerapan Teori MSA pada Teks Perikatan Jual-Beli Notaris - Kurniamala Niswariyana, Ahyati (International Seminar on Austronesian Languages and Literature, 2021)
Notary deed is a written text that becomes authentic evidence in every legal action (one of which is proof of ownership). The deed made by a notary has clear legal force because it has been regulated in the laws and regulations or standard legal regulations. As a text, a deed can be analyzed by linguistic theory. One of the theories in linguistics that can dissect notary deeds is the NSM theory developed by Anna Wierzbicka and her colleague Goddard. The main point of the NSM theory is based on the original meaning. The purpose of this study is to analyze the notarial deed of sale and purchase with the NSM theory. This study applies a qualitative approach using the listen method in collecting data, the agih method to analyze the data, and the informal method to present the results of the data analysis. The results found are the proven NSM theory can be used to reveal semantic phenomena in notarial deed of sale and purchase. The original meaning of the words contained in the notarial deed is quite varied so that it is clear that the meaning of the verbs differs from one another. It turns out that words that have been often juxtaposed with clauses in notarial deed tend to be considered to have the same meaning, after being analyzed with the NSM theory, it can be seen that the differences are quite far from each of these verbs